2004
DOI: 10.1111/j.1439-0396.2004.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Pectin in pig nutrition, a comparative review

Abstract: A comprehensive review is given on pectin effects in pigs. Its effects on feed passage and digestion in the small intestine, the composition of ileal digesta and fermentation in the colon are described. Pectins promote fermentation at the terminal ileum and in the first part of the colon. It is shown, that pectin opposite to cellulose is degraded to high extents in the colon. Dietetic effects in relation to composition of ileocaecal digesta, endogenous secretions, buffering and pH-stability, high fermentabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 62 publications
4
43
1
Order By: Relevance
“…This ingredient is high in soluble fiber, and most of this fiber is pectin, which is highly fermentable in the digestive tract of pigs (Drochner et al, 2004). The same result was verified by Freire et al (2000) and Schavion et al (2004), who evaluated beet pulp in piglets, which is rich in soluble fiber, compared to other fibrous ingredients such as wheat bran, soybean hulls, and alfalfa meal.…”
Section: Assaymentioning
confidence: 60%
“…This ingredient is high in soluble fiber, and most of this fiber is pectin, which is highly fermentable in the digestive tract of pigs (Drochner et al, 2004). The same result was verified by Freire et al (2000) and Schavion et al (2004), who evaluated beet pulp in piglets, which is rich in soluble fiber, compared to other fibrous ingredients such as wheat bran, soybean hulls, and alfalfa meal.…”
Section: Assaymentioning
confidence: 60%
“…Although Stagonias & Pearce (1985) and Drochner et al (2004) reported that transit time is influenced by the level of fiber in the diet, the transit time of diets in the gastrointestinal tract (Table 3) was not influenced (P>0.05) by the inclusion of different fiber sources. An increase in the gastrointestinal transit time may be associated with the type of fiber present in the diet, in addition to other physical characteristics of the feed, such as particle size, amount of fiber ingested and animal weight (Castro Júnior et al, 2005).…”
Section: Resultsmentioning
confidence: 89%
“…An increase in the gastrointestinal transit time may be associated with the type of fiber present in the diet, in addition to other physical characteristics of the feed, such as particle size, amount of fiber ingested and animal weight (Castro Júnior et al, 2005). Drochner et al (2004) with the amount of soluble fiber (pectin) in the food, because this fraction may reduce the pH of the stomach and, consequently, retard the arrival of the digesta in the duodenum, as well as enhance viscosity, thus contributing to increasing in transit time of diets in the gastrointestinal tract. Freire et al (2000) used different fiber sources (wheat bran, beet pulp, soybean hulls, alfafa meal) in the diet of weaned piglets and observed reduction in the transit time when animals received alfafa meal in their diet.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of xylan and wheat bran, high acetate levels are a consequence of low hydrolysis rates that limit the release of monosaccharides. For pectin, this is due to the production of extracellular pectinolytic enzymes (Drochner et al, 2004). The extracellular release of oligosaccharides benefit microbial competitors and reduce the growth of pectinolytic bacteria.…”
Section: Figurementioning
confidence: 99%
“…Methoxylation decreases the growth rate of pectin-fermenting bacteria (Olano-Martin et al, 2002). The methyl group can be esterified with a release of methanol (Drochner et al, 2004) but, unlike glucuronic acid, the methyl group is unusable by pectinolytic bacteria (Hall and Herejk, 2001) for ATP generation and growth.…”
Section: Figurementioning
confidence: 99%